2018
DOI: 10.1007/s11739-018-1806-1
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial hemorrhage in anticoagulated patients with mild traumatic brain injury: significant differences between direct oral anticoagulants and vitamin K antagonists

Abstract: Prognosis after mild traumatic brain injury (MTBI) on oral anticoagulant therapy (OAT) is uncertain. We evaluated the rate of immediate and delayed traumatic intracranial hemorrhage (ICH) comparing vitamin K antagonists (VKAs) to direct oral anticoagulants (DOACs) and the safety of a clinical management protocol. In this single-center prospective observational study, we enrolled 220 patients on OAT with MTBI. After a first negative CT scan, asymptomatic patients underwent a close neurological observation; if n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 35 publications
4
20
1
Order By: Relevance
“…In adults, observation has been shown to be as effective as the CT in the presence of a caregiver and a patient able to understand home instructions [ 46 ]. Our results show similar percentages of positive second CTs of the brain as previous studies [ 20 , 43 , 46 , 59 , 62 , 63 , 64 , 65 , 66 ]. In addition, even our patients who tested positive for the second CTs did not require surgery, as another study showed.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In adults, observation has been shown to be as effective as the CT in the presence of a caregiver and a patient able to understand home instructions [ 46 ]. Our results show similar percentages of positive second CTs of the brain as previous studies [ 20 , 43 , 46 , 59 , 62 , 63 , 64 , 65 , 66 ]. In addition, even our patients who tested positive for the second CTs did not require surgery, as another study showed.…”
Section: Discussionsupporting
confidence: 91%
“…Patient management for those on VKAs and DOAC does not differ, and the observation period is 24 h. This involves resource utilization and a longer stay in ED, as demonstrated by the long LOS ( Table 3 ). However, the need for a control head CT scan in patients on anticoagulation therapy that do not display neurological deterioration is disputable, since the incidence of late ICH is between 0 and 7% [ 20 , 43 , 46 , 59 , 62 , 63 , 64 , 65 , 66 ]. Some countries, such as Italy, have guidelines stating that all anticoagulated patients who have undergone a head CT should be observed for 24 h and have a repeat CT before discharge; others suggest discharge only after observation or observation in the community.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prognosis after mild traumatic brain injury (MTBI) on OACs is uncertain. In the article entitled "Intracranial hemorrhage in anticoagulated patients with mild traumatic brain injury: significant differences between direct oral anticoagulants and vitamin K antagonists", Alessandro Cipriano and colleagues [8] evaluate the rate of immediate and delayed traumatic intracranial hemorrhage (ICH) and the safety of a clinical management protocol in a single-center prospective observational study, enrolling 220 patients on OACs with MTBI. As expected, DOACs are safer than VKAs also in the setting of MTBI.…”
mentioning
confidence: 99%